Use of Artificial Intelligence Tools in the Reinvention of Narratives on TikTok - Barrajón Lara, Iris; Sidorenko Bautista, Pavel; López Serrano, Aida; Lacasa, Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Artificial intelligence (AI) has burst onto TikTok through filters and generative media. This study analyzes 5,000 TikTok videos tagged with #AI, focusing on how AI affects content creation and narratives. Using a mixed method - scanning, visualization, and thematic analysis - we identify the main applications of AI that enhance creativity, personalize content, and blur the boundaries between reality and fiction. Our findings reveal three emerging categories of AI-driven storytelling: rooted content, transformed reality, and new fictional worlds. This research contributes to understanding the evolving role of AI in participatory media and digital culture.